Pyramiding of drought yield QTLs into a high quality Malaysian rice cultivar MRQ74 improves yield under reproductive stage drought - Shamsudin, Noraziyah Abd Aziz; Swamy, B.P. Mallikarjuna; Ratnam, Wickneswari; Sta. Cruz, Ma. Teressa; Sandhu, Nitika; Raman, Anitha K.; Kumar, Arvind (Springer, 2016)
With the objective of improving the grain yield (GY) of the Malaysian high quality rice cultivar MRQ74 under reproductive stage drought stress (RS), three drought yield QTLs, viz. qDTY 2.2, qDTY 3.1 , and qDTY 12.1 were pyramided by marker assisted breeding (MAB). Foreground selection using QTL specific markers, recombinant selection using flanking markers, and background selections were performed in every generation. BC1F3 derived pyramided lines (PLs) with different combinations of qDTY 2.2, qDTY 3.1 , and qDTY 12.1 were evaluated under both RS and non-stress (NS) during the dry season (DS) of 2013 and 2014 at IRRI. The GY reductions in RS trials compared to NS trials ranged from 79 to 99 %. Plant height (PH) was reduced and days to flowering (DTF) was delayed under RS. Eleven BC1F5 MRQ74 PLs with yield advantages of 1009 to 3473 kg ha−1 under RS and with yields equivalent to MRQ74 under NS trials were identified as promising drought tolerance PLs. Five best PLs, IR 98010-126-708-1-4, IR 98010-126-708-1-3, IR 98010-126-708-1-5, IR 99616-44-94-1-1, and IR 99616-44-94-1-2 with a yield advantage of more than 1000 kg ha−1 under RS and with yield potential equivalent to that of MRQ74 under NS were selected. The effect of three drought grain yield QTLs under RS in MRQ74 was validated. Under NS, PLs with two qDTY combinations (qDTY 2.2 + qDTY 12.1 ) performed better than PLs with other qDTY combinations, indicating the presence of a positive interaction between qDTY 2.2 and qDTY 12.1 in the MRQ74 background. Conclusion: Drought tolerant MRQ74 PLs with a yield advantage of more than 1000 kg ha−1 under RS were developed. Differential yield advantages of different combinations of the qDTYs indicate a differential synergistic relationship among qDTYs